Vascular macrophages as therapeutic targets to treat intracranial aneurysms - Muḥammad, Sajjad; Chaudhry, Shafqat Rasul; Dobreva, Gergana; Lawton, Michael T.; Niemelä, Mika; Hänggi, Daniel (Frontiers in immunology, 2021)
Aneurysmal subarachnoid hemorrhage (aSAH) is a highly fatal and morbid type of hemorrhagic strokes. Intracranial aneurysms (ICAs) rupture cause subarachnoid hemorrhage. ICAs formation, growth and rupture involves cellular and molecular inflammation. Macrophages orchestrate inflammation in the wall of ICAs. Macrophages generally polarize either into classical inflammatory (M1) or alternatively-activated anti-inflammatory (M2)-phenotype. Macrophage infiltration and polarization towards M1-phenotype increases the risk of aneurysm rupture. Strategies that deplete, inhibit infiltration, ameliorate macrophage inflammation or polarize to M2-type protect against ICAs rupture. However, clinical translational data is still lacking. This review summarizes the contribution of macrophage led inflammation in the aneurysm wall and discuss pharmacological strategies to modulate the macrophageal response during ICAs formation and rupture.